A new hard phase and physical properties of Tc2C predicted from first principles. Issue 70 (12th July 2016) - Zhang, Gangtai; Zhao, Yaru; Bai, Tingting; Wei, Qun; Yuan, Yuquan
Abstract : Using the first principles particle swarm optimization algorithm for crystal structural prediction, we have predicted a hexagonal P 63 / mmc structure of Tc2 C. Abstract : Using the first principles particle swarm optimization algorithm for crystal structural prediction, we have predicted a hexagonal P 63 / mmc structure of Tc2 C. The new phase is mechanically and dynamically stable, as verified by its elastic constants and phonon dispersion. The formation enthalpy–pressure curves show that the predicted P 63 / mmc -Tc2 C is more energetically favorable than the previously proposed Mo2 C-, anti -MoS2 -, Re2 P-, and Fe2 N-type structures in the considered pressure range. The calculated mechanical properties show that it is an ultra-incompressible and hard material. Meanwhile, the directional dependences of the Young's modulus, bulk modulus, and shear modulus for Tc2 C are systematically investigated. The analyses of the density of states and electronic localization function reveal the presence of strong covalent bonding between Tc and C atoms, which is of crucial importance in forming a hard material.